Case Reports on Severe Antituberculosis-Drug Induced Hepatotoxicity in Tuberculosis Patients: The Post-Incidence Therapy - Nasrawati Basir; Yulia Yusrini Djabir; Arif Santoso (Nusantara Medical Science Journal, 2020)
Introduction:  The first-line regimen for tuberculosis (TB) treatment comprises Isoniazid, Rifampicin, Pyrazinamide, and Ethambutol. However, these drugs are known to potentially cause hepatotoxicity. This study aimed to evaluate hepatotoxicity incidence in patients during intensive phase of anti-tuberculosis treatment focusing on post-incidence therapy. Methods:  The study involved pulmonary TB patients who were admitted to the National Lung Health Center due to hepatotoxicity after receiving fixed-dose combination of antituberculosis drugs (FDC-AT) in September-October 2019. Drug-related hepatotoxicity is defined as an increase in serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST) levels greater than 2.5 times of the normal upper limit (ULN) with an increase in bilirubin level. Results:  There were 8 patients admitted to the center due to hepatotoxicity, 4 of them experienced grade 3 (severe) hepatotoxicity, during which the ALT, AST, bilirubin levels increased 5-10 times of the ULN. The post-hepatotoxicity treatment includes the cessation of FDC-AT treatment followed by hepatoprotective supplements. Following two weeks of treatments, the biomarker levels of two out of four patients went back to normal and the AT therapy was resumed. Meanwhile, the other two patients continued to receive the hepatoprotective therapy for up to 8 weeks. However, when the treatment failed to bring the transaminase level back to normal, a different AT regimen was prescribed. Conclusions: The cessation of FDC-AT and the use of hepatoprotective supplements for two to eight weeks were able to alleviate the AT-induced severe hepatotoxicity. A close monitoring of liver biomarkers is warranted to prevent the incidence of hepatotoxicity in patients receiving antituberculosis